Understanding long COVID: prevalence, characteristics, and risk factors in the Eastern Province of Saudi Arabia - Aldhawyan, Adam F.; BuSaad, Mohammed A.; Almaghlouth, Nawaf E.; Alnasser, Abdullah H.; Alnasser, Jomana A.; Almansour, Abdulelah H.; AlHarkan, Khalid S. (Frontiers in Medicine, 2024)
Background The COVID-19 pandemic has significantly raised public health concerns and efforts to limit its spread, impacting societies and health systems worldwide. As challenges persist, the emergence of Long COVID (LC) marks a turning point in understanding the pandemic’s long-term effects. Aim This study aimed to determine the prevalence of LC in the Eastern Province of the Kingdom of Saudi Arabia (KSA) and explore factors contributing to its persistence. Methods This descriptive, cross-sectional, questionnaire-based study was carried out between December 1, 2023, and March 1, 2024, involving 1,355 patients who recovered from COVID-19. Participants were conveniently chosen and information was gathered through in-person interviews in public settings after obtaining consent. Results A majority of the patients (N = 1,355; 47.5% female; 93.8% Saudis; mean Age ± SD 33.13 ± 12.60 years) had received three COVID-19 vaccine doses (89.5%). Women experienced 17.4% more LC symptoms than men (p < 0.001). The risk of having a higher symptom count increased by 42.5% 12 months after acute COVID-19 infection compared with baseline (<3 months, p < 0.001). A higher body mass index (BMI) was associated with more symptoms (1.1% increase per unit, p = 0.004). More acute-phase symptoms correlated with more LC symptoms (p < 0.001). Higher educational attainment reduced LC risk by 33% (p < 0.001). Finally, age and vaccination status had no effect on LC symptoms count (p > 0.05). Conclusion Sociodemographic and clinical factors contribute differently to the chances of having LC and the count of symptoms. Awareness of such factors could provide insight into improving management, leading to better health outcomes.